OPTIMALISASI PERAN WAKAF DALAM PEMBERDAYAAN USAHA MIKRO, KECIL DAN MENENGAH (UMKM) - Cantika, Sri Budi (Faculty of Economics and Business, University of Muhammadiyah Malang, 2015)
The potential of Zakat, Infaq, Shodaqoh (ZIS), and Waqaf (endowments) to help society economic improvement are very important, yet the role of Islamic Finance Institution, as the executing agency that administer these four pious deed, were still not optimal yet. This article reveals the important role of Endowments in assisting the empowerment of Micro, Small, and Medium Enterprises (MSMEs) which is one of the strengths in poverty alleviation, employment creation and increase the strength of family income. Waqaf (endowments) Management Institute, an organization that empowers MSMEs through microfinance and business assistance, offers some strategic steps that must be carried out in managing successful business namely providing investment capital and working capital, presenting training and skills improvement, business consulting, improving product quality, market, business networking, and technology.